Greener approach for goat skin tanning. Issue 1 (31st December 2022) - Seda Badessa, Tolera; Hailemariam, Mihret Tekalign; Ahmed, Shegaw Mohammed
Abstract: Chrome tanned leather accounts for 90% of leather in the world. However, chromium is a global environmental disaster and puts the health of millions of leather workers and ordinary citizens at risk. The use of natural materials that is eco-friendly on leather as vegetable tanning is therefore, a matter of significant importance. Thus, the current study focused to investigate the potential effectiveness of the extracted tannin from Sodom apple (Solanum Incanum) fruit as vegetable tanning agent on goatskins. It was extracted with distilled water, methanol, petroleum ether and ethanol by using Soxhlet extraction method. Although the amount of material extracted was significant in all extracting solvents, water was a more efficient solvent (extraction yield of 16.71%) than the others. The qualitative analysis and structural characterization of the extracts were done using thin-layer chromatography (TLC), Ultraviolet (UV) spectrometer and Fourier Transform Infrared (FT-IR) spectrometer which confirmed the presence of condensed tannins in the extract. The Scanning Electron Microscope (SEM) was carried out to study the effect of the tannin system on the structural and morphological characteristics of the tanned leathers. Similarly, the organoleptic and strength properties of the tanned leathers were evaluated in comparison with the control ones. Finally, the pollution load of tanning liquors in Sodom apple tanning was significantly reduced as compared to the control (mimosa). Hence, from the current study, it is possible to conclude that Sodom apple fruit extract is a cleaner alternative and promising pathway for goatskin tanning.